Influence of antithrombotic agents on the recurrence of chronic subdural hematomas and the quest about the recommencement of antithrombotic agents: A meta-analysis. (April 2017) - Wang, Yangshuo; Zhou, Jingru; Fan, Cungang; Wang, Dongliang; Jiao, Feng; Liu, Bo; Zhang, Qingjun
Highlights: A meta-analysis on the postoperative recurrence rate of chronic subdural hematoma. Anticoagulants and antiplatelets are risk factors for postoperative recurrence. Appropriate postoperative resumption of anticoagulants or antiplatelets may be safe. The resumption does not appear to increase postoperative complications. Abstract: Antithrombotic agents (AT), including anticoagulants and antiplatelets, are risk factors of chronic subdural hematomas (CSDHs). However, the use of AT has not been clearly associated with postoperative recurrence (PR) in the literature before. Furthermore, the association between the resumption of AT and postoperative complications also requests research. Databases including Pubmed, Embase and Cochrane were searched for patients presenting with CSDH on anticoagulant or antiplatelet medication. Ten studies were included to analyze the association between the use of AT and PR: The meta-analysis showed that the use of AT, both anticoagulants (OR = 2.20, 95%CI [1.45, 3.33]; P = 0.0002) and antiplatelets (OR = 1.64, 95%CI [1.17, 2.30]; P = 0.004), could increase the PR rate. Two studies were included to analyze the relationship between the resumption of AT and postoperative complications. The meta-analysis showed that after the patients on AT resumed their medication, the risk of PR did not increase (OR = 0.33, 95%Cl [0.13, 0.80]; P = 0.01), and the occurrence of thromboembolism events had no statistical significance (OR = 1.30, 95%CI [0.26, 6.50]; P = 0.75). This meta-analysis demonstrated that AT were risk factors for the recurrence of CSDH. Recommencement of AT did not appear to increase the risk of postoperative hemorrhage, and could reduce the risk of thromboembolism. Thus, appropriate postoperative resumption of anticoagulants or antiplatelets may be safe. Still, more evidence is needed to answer the question about whether and how to resume AT.